Pengaruh Risiko Audit, Time Budget Pressure dan Rotasi KAP terhadap Kualitas Audit: Studi Empiris pada Perusahaan Sektor Keuangan yang Terdaftar di BEI - Zikra Ilhamullah; Salma Taqwa (Universitas Negeri Padang, 2026)
The purpose of this study is to examine how audit risk, time budget pressure, and audit firm rotation affect audit quality. This study uses a quantitative method. The company's annual report, taken from the Indonesia Stock Exchange website and the intended company, serves as the source of research data. Using a purposive sampling technique, this study collected 174 samples between 2020 and 2022 from 58 financial companies. This study uses logistic regression analysis to test the hypothesis. The research findings indicate that time budget pressure has an effect on audit quality, while audit risk and audit firm rotation have no effect on audit quality.